2015
DOI: 10.1111/jerd.12149
|View full text |Cite
|
Sign up to set email alerts
|

Color Difference Thresholds in Dentistry

Abstract: Visual color difference thresholds can serve as a quality control tool to guide the selection of esthetic dental materials, evaluate clinical performance, and interpret visual and instrumental findings in clinical dentistry, dental research, and subsequent standardization. The importance of quality control in dentistry is reinforced by increased esthetic demands of patients and dental professionals.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

49
1,091
16
54

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 894 publications
(1,210 citation statements)
references
References 33 publications
49
1,091
16
54
Order By: Relevance
“…25 This means that 50% of observers will note a perceptual difference between two colors when the DE* is 1.2. Similarly, 50% of observers will determine a color difference to be acceptable at a DE* of 2.7, while the other 50% will consider this color difference unacceptable.…”
Section: Discussionmentioning
confidence: 99%
“…25 This means that 50% of observers will note a perceptual difference between two colors when the DE* is 1.2. Similarly, 50% of observers will determine a color difference to be acceptable at a DE* of 2.7, while the other 50% will consider this color difference unacceptable.…”
Section: Discussionmentioning
confidence: 99%
“…Here, we used the CIE L * a * b * system to evaluate ΔE * . Although some recent studies have demonstrated that another measurement system, i.e., CIEDE2000, may provide a better fit than the former in the evaluation of color difference thresholds, 10,18,19,20 many other studies use the CIE L*a*b* color system to analyze color outcomes in dentistry 3,5,21,22,23 because this system features predictability and clinical importance. ΔE * did not increase after 12 months of storage in specimens prepared with the modeling liquids.…”
Section: Discussionmentioning
confidence: 99%
“…26 ∆E of all groups exceeded the threshold established for color acceptability in dentistry (∆E =2.7). 25 Furthermore, ∆E and opacity of the Nosi and Si groups increased as more amount of ZnOnps was added into PMMA. These changes in the optical characteristics of a material are a common disadvantage of incorporating metal oxide into PMMA.…”
mentioning
confidence: 99%
“…The most commonly utilized color system for color assessment is the CIELAB system, which defines the color characteristics as L*, a*, and b*. [20][21][22][23][24][25][26] L* represents brightness, a* represents the red-green coordinates, and b* represents the yellow-blue coordinates. The CIELAB system can mathematically express the color difference (∆E) between the two objects.…”
Section: Introductionmentioning
confidence: 99%